Inhibiting concentration quenching in Yb3+-Tm3+ upconversion nanoparticles by suppressing back energy transfer - Dingxin Huang; Feng Li; Hans Ågren; Guanying Chen (Nature Communications)
Abstract Lanthanide-doped upconversion nanoparticles are promising for applications ranging from biosensing, bioimaging to solid-state lasing. However, their brightness remains limited by the concentration quenching effect of lanthanide activator ions, which greatly restricts their utility. Here, we develop a heterogeneous core–shell–shell nanostructure based on hexagonal NaYF4, in which Tm3+ activator and Yb3+ sensitizer are separated into the core and inner shell, while the outmost shell is used to suppress surface quenching effects. We show that this design can alleviate the activator concentration quenching effect, resulting in optimal Tm3+ concentration increasing from 1% to 8% at sub-100 W/cm2 irradiance, compared with the canonical core-only NaYF4:Yb3+/Tm3+. Moreover, under high excitation irradiance (20 MW/cm2), the optimal Tm3+ concentration could be further increased to 50%. Mechanistic investigations reveal that the spatial separation of sensitizer and activator effectively suppresses the back energy transfer from Tm3+ to Yb3+, driving the increase of optimal activator concentration. These findings enhance our understanding of lanthanide concentration quenching effect, unleashing opportunities for developing bright upconverting materials.